Studi Kasus: Asuhan Keperawatan Keluarga Dengan Penerapan Foot Massage Pada Lansia Dengan Hipertensi - Hasan, Utari; Saputra, Candra; Sriyani Harahap, Afrida; Ezalina, Ezalina (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Elderly individuals are those who are over 60 years old. Older individuals often develop hypertension due to the stiffening and loss of flexibility in their blood vessels with age.  Consequently, the heart must exert more effort to circulate blood, resulting in elevated blood pressure. Purpose  of this final nursing thesis is to provide an overview of the results of the Nurse Profession practice with the application of family nursing care through foot massage therapy for the nursing problem of ineffective family health management in elderly individuals with hypertension in Sungai Putih Village, Tapung District, Kampar Regency. Method : The method used is a case study, involving the administration of Foot Massage therapy to individuals with hypertension. The writing will take place from February 15 to 20, 2025. The foot massage is performed day for 3 days, with each session lasting 6 minutes, and each foot receiving 3 minutes of massage. This case study demonstrates that after three days of foot massage treatment, there is a considerable disparity in the family's efficacy in executing the required tasks before and after the therapy.  Moreover, a notable disparity exists in pain severity before to and during foot massage treatment in older persons with hypertension. The application of Foot Massage is very effective in elderly hypertension if done regularly can lower blood pressure. Foot massage or foot massage can be an effective non-pharmacological therapy to lower blood pressure in people with hypertension. Foot massage can provide a relaxing effect that can smooth blood flow and body fluids, and relieve stress that can increase blood pressure.